2014
DOI: 10.1111/mmi.12650
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles produced by the Gram‐positive bacterium Bacillus subtilis are disrupted by the lipopeptide surfactin

Abstract: Summary Previously, extracellular vesicle production in Gram-positive bacteria was dismissed due to the absence of an outer membrane, where Gram-negative vesicles originate, and the difficulty in envisioning how such a process could occur through the cell wall. However, recent work has shown that Gram-positive bacteria produce extracellular vesicles and that the vesicles are biologically active. In this study, we show that Bacillus subtilis produces extracellular vesicles similar in size and morphology to othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
152
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(177 citation statements)
references
References 37 publications
12
152
1
1
Order By: Relevance
“…It has been suggested that the vesicles produced by monoderm bacteria are like their diderm counterparts, involved in pathogenesis (Rivera et al 2010;Prados-Rosales et al 2011). Enzymes involved in peptidoglycan degradation, antibiotic degradation, virulence factors (anthrolysin, anthrax toxin components, coagulases, hemolysins and lipases) and immunologically-active compounds have been identified in these vesicles (Marsollier et al 2007;Lee et al 2009;Rivera et al 2010;Gurung et al 2011;Prados-Rosales et al 2011;Thay et al 2013;Brown et al 2014).…”
Section: Emvs In Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the vesicles produced by monoderm bacteria are like their diderm counterparts, involved in pathogenesis (Rivera et al 2010;Prados-Rosales et al 2011). Enzymes involved in peptidoglycan degradation, antibiotic degradation, virulence factors (anthrolysin, anthrax toxin components, coagulases, hemolysins and lipases) and immunologically-active compounds have been identified in these vesicles (Marsollier et al 2007;Lee et al 2009;Rivera et al 2010;Gurung et al 2011;Prados-Rosales et al 2011;Thay et al 2013;Brown et al 2014).…”
Section: Emvs In Bacteriamentioning
confidence: 99%
“…OMVs are potent virulence factors of pathogenic diderm bacteria. These vesicles contain toxins, DNA, immunomodulatory compounds, communication factors and adhesins, and have been associated with cytotoxicity, bacterial attachment, intercellular DNA transfer and invasion (Dorward et al 1989;Kuehn & Kesty 2005;Ellis & Kuehn 2010;Maldonado et al 2011;Brown et al 2014). Increased vesiculation has been linked to bacterial stress and may play a role in carrying away toxic compounds, phages or unfolded proteins after exposure to stressful conditions (McBroom & Kuehn 2007;Macdonald & Kuehn 2013).…”
Section: Emvs In Bacteriamentioning
confidence: 99%
“…Previous studies have revealed that MV release is conserved in Gram-negative cells and that MVs are associated with virulence factor delivery, protein secretion, cell-cell communication, protection from phage infection, and other biological processes (2,8). Although Gram-positive bacteria have no outer membrane and are covered by a rigid, thick cell wall, MV production was observed in many Gram-positive bacteria, such as Bacillus subtilis, Staphylococcus aureus, Listeria monocytogenes, Streptococcus mutans, S. pneumoniae, Mycobacteria spp., and Lactobacillus rhamnosus (14)(15)(16)(17)(18)(19)(20)(21). In addition, Grampositive bacterial MVs have been reported to deliver virulence factors to host cells to stimulate an immune response in recipient cells and to facilitate biofilm formation by extracellular DNA release via the MVs (17,22,23), suggesting that functional MV release is also conserved in Gram-positive bacteria.…”
mentioning
confidence: 99%
“…Only a few factors involved in MV production have been reported in Gram-positive bacteria. The biosurfactant surfactin and serum albumin disrupt Gram-positive bacterial MVs (14,25), suggesting that the amount and the local concentration of MVs are controlled by the bacterial and host environments. In Mycobacterium tuberculosis, virR mutant strains overproduce MVs; thus, VirR proteins inhibit vesiculogenesis (26).…”
mentioning
confidence: 99%
“…Recently, it was shown that B. subtilis disrupts its own EVs by secreting surfactin (79). The targeted lysis of EVs by surfactin may serve as a defensive mechanism against antibiotic-laden vesicles produced by competing organisms or as an offensive tool to prevent nonpolar signaling molecules, including quorum sensors, from reaching their intended targets.…”
mentioning
confidence: 99%